Gazing beyond the fourth wall: shame and second-person narration in Fleabag. Issue 10 (3rd October 2022) - Wong, Denise
ABSTRACT: This essay explores how structures of looking and parabasis in Fleabag replicate the second-person pronoun's ability to interpellate a storyworld-external reader in textual narrative, and the extent to which it may be considered a televisual example of second-person narrative. Using David Herman's typology of narrative- you, I argue that Phoebe Waller-Bridge's use of the camera in Fleabag creates the impression of an addressee that is both inside and outside the diegesis. This gaze reproduces the ontological hesitation which characterises Herman's notion of the doubly deictic you. Fleabag 's use of parabasis to cross the narrative threshold consequently produces a temporal schism between what Bergson describes as the perception of a moment as it happens and the reflection of it as though it has already happened. Crucially, this doubleness is particular to both the doubleness in the structure of shame according to Sartre and the double deixis of the second-person mode more broadly. Waller-Bridge's use of parabasis serves as an original contemporary case study for advancing critical discussions of second-person narrative theory in relation to temporality and affect.